Molecular cloning and functional identification of a cDNA encoding 4-hydroxy-3-methylbut-2-enyl diphosphate reductase from Tripterygium wilfordii - Qiqing Cheng; Yuru Tong; Zihao Wang; Ping Su; Wei Gao; Luqi Huang (Acta Pharmaceutica Sinica B, 2017)
The 4-hydroxy-3-methylbut-2-enyl diphosphate reductase (HDR) is the last step key enzyme of the methylerythritol phosphate (MEP) pathway, synthesizing isopentenyl diphosphate and its allyl isomer dimethylallyl diphosphate, which is important for regulation of isoprenoid biosynthesis. Here the full-length cDNA of HDR, designated TwHDR (GenBank Accession No. KJ933412.1), was isolated from Tripterygium wilfordii for the first time. TwHDR has an open reading frame (ORF) of 1386 bp encoding 461 amino acids. TwHDR exhibits high homology with HDRs of other plants, with an N-terminal conserved domain and three conserved cysteine residues. TwHDR cDNA was cloned into an expression vector and transformed into an Escherichia coli hdr mutant. Since loss-of-function E.coli hdr mutant is lethal, the result showed that transformation of TwHDR cDNA rescued the E.coli hdr mutant. This complementation assay suggests that the TwHDR cDNA encodes a functional HDR enzyme. The expression of TwHDR was induced by methyl-jasmonate (MJ) in T. wilfordii suspension cells. The expression of TwHDR reached the highest level after 1 h of MJ treatment. These results indicate that we have identified a functional TwHDR enzyme, which may play a pivotal role in the biosynthesis of diterpenoid triptolide in T. wilfordii.